P.032 What do elective students learn about the specialty of Neurology (and what can that teach us)?. (June 2019) - Moore, F
Abstract : Background: "Neurophobia" describes a fear of Neurology on the part of medical students. This contrasts with the "neurophilia" that exists in society with increasing awareness of disorders such as stroke and multiple sclerosis. Ideally, we should take advantage of "neurophilia" to promote our specialty's strengths. One step would be to better understand what students learn from a Neurology elective. Methods: This was a qualitative study. Students completing an elective between September 2011 and March 2015 at the Jewish General Hospital (JGH) in Montreal completed written pre- and post-elective questionnaires. Results: 36 students participated; 15 from McGill, 11 from other Canadian medical schools, and 10 from International medical schools. Many students changed their opinion about Neurology, with fewer citing lack of treatments or poor patient prognoses as negatives after completing their elective. They valued knowledge acquired about the neurological exam and problem-solving, while the range of cases and subspecialties surprised them. Many would diversify the setting of their elective to better experience this variety. Conclusions: More diversified elective experiences could showcase the strengths of our specialty and the scope of neurological practice. Presenting Neurology as a challenging, intellectually stimulating specialty that emphasizes problem solving could increase student interest.